2013
DOI: 10.1007/s00281-013-0375-7
|View full text |Cite
|
Sign up to set email alerts
|

Low-density granulocytes: a distinct class of neutrophils in systemic autoimmunity

Abstract: Recent studies have renewed the interest on the potential role that neutrophils play in the development of systemic lupus erythematosus (SLE) and other autoimmune conditions. A distinct subset of proinflammatory, low-density granulocytes (LDGs) isolated from the peripheral blood mononuclear cell fractions of patients with SLE has been described. While the origin and role of LDGs needs to be fully characterized, there is evidence that these cells may contribute to lupus pathogenesis and to the development of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
329
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 297 publications
(351 citation statements)
references
References 61 publications
15
329
1
6
Order By: Relevance
“…Accordingly, PAD4-deficient mice are incapable of generating NETs; however, these animals do not phils that have been activated and partially degranulated (36,37). Whether such phenotypic differences are relevant to the ability of these cells to undergo NETosis is not known, but circumstantial evidence points in this direction, as discussed below.…”
Section: Are Nets Important For Immune Defense?mentioning
confidence: 92%
“…Accordingly, PAD4-deficient mice are incapable of generating NETs; however, these animals do not phils that have been activated and partially degranulated (36,37). Whether such phenotypic differences are relevant to the ability of these cells to undergo NETosis is not known, but circumstantial evidence points in this direction, as discussed below.…”
Section: Are Nets Important For Immune Defense?mentioning
confidence: 92%
“…Neutrophils exposed to ribonucleoprotein immune complexes are liable to undergo NETosis through the induction of mitochondrial reactive oxygen species (ROS) [34]. Moreover, SLE patients have a distinct subset of proinflammatory neutrophils, lowdensity granulocytes (LDGs) [35], which have an enhanced capacity of forming NETs [20] and synthesizing mitochondrial ROS [34]. Taken together, all these studies provide convincing evidence that NETosis is one of the major sources of self-dsDNA, and a defect in NETs clearance plays an important role in SLE pathogenesis.…”
Section: Self-dsdna Released Through Netsmentioning
confidence: 99%
“…Villanueva et al (46) showed that low-density granulocytes spontaneously can form NETs. Low-density granulocytes are a neutrophil subset that can be found in the mononuclear cell fraction, and they have been reported to be present in all SLE patients (48). Comparing gene array profiles of low-density granulocytes to normal density neutrophils showed that low-density granulocytes significantly overexpressed mRNA of various immunostimulatory bactericidal proteins and alarmins, relative to lupus neutrophils and control neutrophils.…”
Section: Hmgb1 and Netsmentioning
confidence: 99%